Plastics pyrolysis: The impact of pyrolysis temperature on ethylene production and direct carbon dioxide footprint - Ruben J. de Korte; Melissa N. Dunkle; Ramon van Belzen; Alessandro Battistella; George Bellos (Fuel Processing Technology)
An attempt to estimate the energy and emissions for chemically recycling polyethylene is presented. The workflow includes an experimental section to generate pyrolysis decomposition data, and a process model to simulate the process. Pyrolysis coupled to gas chromatographic separation with mass spectrometric and flame ionization detection (Pyr-GC–MS/FID) was carried out at different temperatures, ranging from 600 to 800 °C on both low-density polyethylene (LDPE) pellets and linear low-density (LLDPE) pellets. The hydrocarbon composition of the pyrolyzed materials was determined using the MS data, while quantification was performed using the FID data. The quantified hydrocarbon composition was then used as the input data for modeling the pyrolysis reactor and separations process in Aspen Plus. The direct CO2 emissions were estimated for downstream chemical processes, such as pyrolysis oil hydroprocessing, steam cracking, and polymerization. The process analysis included the evaluation of scenarios where the pyrolysis plant was located in a stand-alone site and integrated with surrounding chemical plants. It was shown that higher pyrolysis temperatures create the possibility for collocating a pyrolysis plant with the steam cracker process.